Synergistic activity of sorafenib and sulforaphane abolishes pancreatic cancer stem cell characteristics - Rausch, Vanessa; Liu, Li; Kallifatidis, Georgios; Baumann, Bernd; Mattern, Jürgen; Gladkich, Jury; Wirth, Thomas; Schemmer, Peter; Büchler, Markus W.; Zöller, Margot; Salnikov, Alexey V.; Herr, Ingrid (Cancer research, 2010)
Recent evidence suggests that pancreatic cancer and other solid tumors contain a subset of tumorigenic cells capable of extensive self-renewal that contribute to metastasis and treatment resistance. Sorafenib (SO) is a promising new multikinase inhibitor for treatment of advanced kidney and liver cancers. We report here targeting of pancreatic cancer stem cells (CSC) by SO and the development of a strategy to enhance this effect. Although SO administration diminished clonogenicity, spheroid formation, aldehyde dehydrogenase 1 (ALDH1) activity, growth on immunodeficient mice, proliferation, and angiogenesis and induced apoptosis, we observed SO-induced activation of NF-κB associated with survival and regrowth of spheroids. For enhanced elimination of CSC characteristics by SO, we cotreated cells with sulforaphane (SF). This broccoli isothiocyanate was recently described to eliminate pancreatic CSCs by downregulation of NF-κB activity without inducing toxic side effects. On combination treatment, SF completely eradicated SO-induced NF-κB binding, which was associated with abrogated clonogenicity, spheroid formation, ALDH1 activity, migratory capacity, and induction of apoptosis. In vivo, combination therapy reduced the tumor size in a synergistic manner. This was due to induction of apoptosis, inhibition of proliferation and angiogenesis, and downregulation of SO-induced expression of proteins involved in epithelial-mesenchymal transition. Our data suggest that SF may be suited to increase targeting of CSCs by SO.
Gesehen am 10.05.2023